Technical Competency for Diploma in Mechatronic Engineering at Polytechnics Malaysia - Hasan, Azman; Mohd Yasin, Sharifah Nurulhuda Tuan; Mohd Yunus, Mohd Fauzi (International Review of Management and Marketing, 2016)
Mechatronics is the combination of Mechanical engineering, Electronic engineering, Computer engineering, Software engineering, Control engineering, and Systems Design engineering in order to design, and manufacture useful products. Mechatronics is a multidisciplinary field of engineering. The paper discusses about the technical competency for Diploma in Mechatronic Engineering at the Polytechnic Graduates. This competency is reference Accreditation Board for Engineering & Technology (ABET) , American Society of Mechanical Engineers (ASME) and Japan Accreditation Board for Engineering Education (JABEE). Competency standards are statements of attainment in specific abilities in the workplace that graduates have to accomplish upon completing their studies in their respective programmes in polytechnics. Competency Standards for the Programme, highlight the standards or statements of attainment to measure accomplishments in the programme of Diploma in Mechatronic Engineering at the Polytechnics. Curriculum development process started by getting feedback from the industry, information from government documents relating and interpreting the results of a needs analysis. In addition, this process also involves designing and providing a program structure, courses and syllabi for courses of study according to the criteria. Statement of the competency standards serve as a guide in preparing the course syllabus for the DEM. Accordingly, the standard of competence is a summary of learning outcomes as described by Course Learning Outcomes in curriculum documents Keywords: Technical Competency, Diploma in Mechatronic Engineering at Polytechnics JEL Classifications: J10, M10